Human Plasma Protein Corona of Aβ Amyloid and Its Impact on IAPP Cross-Seeding - Nandakumar, Aparna (Biomacromolecules, 2020)
Alzheimer’s disease (AD) is the most severe form of neurological disorder, characterized by the presence of extracellular amyloid-β (Aβ) plaques and intracellular tau tangles. For decades, therapeutic strategies against the pathological symptoms of AD have often relied on the delivery of monoclonal antibodies to target specifically Aβ amyloid or oligomers, largely to no avail. Aβ can be traced in the brain as well as in cerebrospinal fluid and the circulation, giving rise to abundant opportunities to interact with their environmental proteins. Using liquid chromatography tandem-mass spectrometry, here we identified for the first time the protein coronae of the two major amyloid forms of Aβ – Aβ(1–42) and Aβ(1–40) – exposed to human blood plasma. Out of the proteins identified in all groups, 58 proteins were unique to the Aβ(1–42) samples and 31 proteins unique to the Aβ(1–40) samples. Both fibrillar coronae consisted of proteins significant in complement activation, inflammation and protein metabolic pathways involved in the pathology of AD. Structure-wise, the coronal proteins often possessed multi domains of high flexibility to maximize their association with the amyloid fibrils. The protein corona hindered recognition of Aβ(1–42) fibrils by their structurally specific antibodies, and accelerated the aggregation but not β-cell toxicity of human islet amyloid polypeptide (IAPP), the peptide associated with type 2 diabetes. This study highlights the importance of understanding the structural, functional and pathological implications of the amyloid protein corona for the development of therapeutics against AD and a range of amyloid diseases.